Javaslatok rétegelt-ragasztott fatartók tervezéséhez, gyártásához és üzemeltetéséhez, felmérési és modellezési eredmények alapján - III. rész A tönkremeneteleket igazoló vizsgálatok és eredményei = Design, fabrication and operation proposals for glued-laminated timber, based on measuring and modelling results - Chapter 2: Failure examinations and their results - Vanya Csilla (FAIPAR, 2016)
A rétegelt-ragasztott fatartók egyre elterjedtebbé váltak az elmúlt 50 évben. A megfelelő minőségű anyagokból készített rétegelt-ragasztott tartók minőségi beszerelést és üzemeltetést követően időtállóak, azonban egyre több esetben fordul elő a rétegelt-ragasztott tartók károsodása és a károsodás miatt egész tetőszerkezetek életveszélyessé válása. Ebben a cikkben a rétegrepedések és tönkremenetelek okaihoz kapcsolódó mechanikai vizsgálatok és azok eredményei kerülnek bemutatásra. A mechanikai vizsgálatok célja, hogy próbatest szinten megállapítsuk a ciklikusan változó klimatikus környezet (hőmérséklet, páratartalom) hatását az RR tartók faanyagára és annak ragasztási síkjaira. Mivel a faanyag rostra merőleges húzószilárdsága és nyírószilárdsága csekély, a tartókon kialakult delamináció oka, ezen feszültségek szilárdságot meghaladó mértékében keresendők. Az elvégzett vizsgálatok is a két szilárdság meghatározására ill. a ciklikusan változó klimatikus környezet ezen szilárdságokra gyakorolt hatására irányultak. = Glue laminated timber beams have been used in an increasing number of cases in the past 50 years. Glue laminated beams are durable constructs if they are manufactured from adequate quality materials and if their installation and operation are performed to a high quality standard. There are however an increasing number of cases of glue laminated beams suffering damage and as a result entire roof structures becoming life-threatening. In this paper we present the mechanical tests and their results related to the causes of delaminations and failures. The purpose of mechanical tests is to determine the impact of the cyclically changing climatic environment (temperature, humidity) on the material and the gluing planes of glued laminated timber structures on a test specimen level. Since timber has low tensile and shear strength normal to grain, the cause of delamination in the structures is to be sought in the excess of stress exceeding the strength. The performed tests focused on the determination of the two strength values and the impact of the cyclically changing climatic environment on these strengths.